Strategi Pembelajaran Bahasa Arab Berbasis Gambar Untuk Meningkatkan Keterampilan Qira’ah Siswa Kelas 1 MI - Oktaviani, Ecca; Jailani, Mohammad (Pimpinan Cabang Muhammadiyah Kramat Jati, 2025)
Arabic language learning in Madrasah Ibtidaiyah (MI) still faces several obstacles besides the geographical factor of the school which is located in a remote area so that appropriate innovation is needed so that it can increase students' interest in learning, if this is allowed to continue then learning seems ineffective and difficult for students to accept. Therefore, an innovative and interesting learning strategy is needed. This study aims to implement a picture-based learning strategy in Arabic language learning for grade 1 at MI, this strategy uses a method of images that are relevant to the learning material to improve student understanding and retention. The results of the study showed that the picture-based learning strategy was able to increase students' interest and motivation higher, students' understanding and focus also improved, and improved Arabic language learning outcomes. Therefore, the strategy of using relevant images can be used as an alternative learning and can also be an additional teaching material for effective and interesting Arabic at MI.